Analysis of Lumbar Sagittal Curvature in Spinal Decompression and Fusion for Lumbar Spinal Stenosis Patients under Roussouly Classification. (5th May 2020) - Zhang, Guoqiang; Yang, Yong; Hai, Yong; Li, Jinjun; Xie, Xuehu; Feng, Shitong
Abstract : To evaluate the clinical significance of spinal decompression and fusion for lumbar spinal stenosis in old patients under Roussouly classification, 160 old patients (>60 year old) with lumbar spinal stenosis underwent spinal decompression, and fusion were retrospectively studied. According to Roussouly classification, patients were divided into 4 groups, in which Roussouly types I, II, and IV were the nonstandard group and Roussouly type III was the standard group. Visual analog scale (waist, leg) and Oswestry disability index (ODI) scores were recorded before operation and at the final follow-up. All patients improved the sagittal curvature: for patients in Roussouly types I and II, there were statistically significant differences in terms of postoperative global lordosis (GL), global kyphosis (GK), sacral slope (SS), sagittal vertical axis (SVA), and pelvic tilt (PT) compared with that before surgery (all P < 0.001 ); patients in Roussouly type IV obtained similar results with type III after surgery. The four groups showed significant improvement in ODI and VAS scores at final follow-up (all P < 0.001 ). After regrouping at the final follow-up, the proportion of the standard type (Roussouly type III) patients was increased compared with preoperative. In conclusion, Roussouly classification has important guiding significance in spinal decompression and fusion for old patients (>60 years) with lumbar spinal stenosis.